The Reasons of low achievement for the High schools ' students in English Language at Tafila Governorate in Jordan from Teachers ' Point of View - AlQuabe'h, Wafa' Abdulrahim (Journal of Educational and Psychological Sciences, 2019)
This study aimed to identify the reasons for the low achievement of high school students in the subject of English in Tafila, Jordan from the point of view of teachers. The study used the descriptive method, and the tool consisted of a questionnaire of (36) items; it was distributed to a sample of (25) teachers of English in Tafila governorate. The data were analyzed in the study using SPSS, and finding arithmetic averages, standard deviations and ranks, and T-test. The tool's overall score was average (3.59 out of 5), rated (large). On the field level, the field of reasons related to students received the highest average; (4.04) followed by the area of reasons related to the teacher with an average (3.62), both with a verbal (large) and thirdly the field of reasons related to the textbook with an average (3.37) and finally the reasons for the evaluation with an average (3.34) Both are rated (medium). The results showed that the reasons for the low level of achievement for the students in the English language are not affected at the level of significance (0.05 = α) by gender variables, and years of experience. the results indicated no significant differences Statistics among teachers' estimates due to their gender, The study also showed that there were no apparent differences between teachers' estimates in the light of variable years of experience, In light of the results, a number of recommendations and suggestions were presented to overcome the causes of the decline and improve the achievement of high school students in the English language in Tafila and the Kingdom.
Keywords: causes of decline; High school student achievement; English language study; Tafila Governorate